Public Relations Strategy in Restoring Corporate Image at PT Toyota Astra Motor - Maria Wandita Utami (Golden Ratio of Data in Summary, 2026)
In an era marked by globalization and increasingly fierce business competition, the company's image has become a strategic asset that significantly affects the trust of customers, business partners, and the wider community. PT Toyota Astra Motor as a leading player in the automotive industry is not immune to reputational risks that may arise from a crisis situation. One notable example is the case of airbag recalls, which poses a serious challenge to the company's public image. This study aims to analyze the image restoration strategy implemented by PT Toyota Astra Motor Indonesia in response to the airbag recall crisis. This research is based on the concepts of communication and public relations, with a special focus on William L. Benoit's Image Restoration Theory. This study emphasizes the role of public relations (PR) in managing crisis communication and mitigating reputational damage. Adopting a qualitative approach, data is collected through various communication channels, including mass media coverage, the company's official website, and exclusive interviews featured on Toyota's official YouTube platform. The findings reveal that PT Toyota Astra Motor uses a proactive, transparent, and strategic PR approach in overcoming the crisis. The company actively engages with mass media and digital platforms, collaborates with credible automotive experts, openly acknowledges these issues, and provides clear and consistent information while encouraging public dialogue. This comprehensive response was positively received by the public, showing that the PR strategy implemented was effective in rebuilding trust and restoring the company's image. The study highlights that transparency, accountability, and active stakeholder engagement are critical components of successful crisis management and can serve as a practical model for organizations facing similar challenges.